Analysis of Nanoparticle Additive Couple Stress Fluids in Three-layered Journal Bearing - T. , V. V. L. N. Rao (2013)
The present theoretical study investigates the load capacity and friction coefficient in a three-layered journal bearing lubricated with nanoparticle additive couple stress fluids. The couple stresses effects are analyzed based on Stokes micro-continuum theory. The nondimensional pressure and shear stress expressions are derived using modified Reynolds equation. The nondimensional load capacity increases and the coefficient of friction decreases using nanoparticle additive lubricants with couple stress effects. The three-layered journal bearing performance characteristics are improved with increase in both (i) surface adsorbent fluid film layer thickness and (ii) dynamic viscosity ratio of surface to core layer.